Development of Prophetic Motion Graphic Animation Videos - Fahma, Naomi; Sumardjoko, Bambang; Prayitno, Harun Joko; Sulistyanto, Hernawan (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2025)
This aim of research to determine the development and effectiveness of motion graphic video for elementary school students in science subjects. This exploratory sequential mixed method research uses a combination of qualitative descriptive methods to define the current situation and product development process as as well as experimental methods in each control and experimental group. This research was conducted in two different selected elementary schools. Researchers used interviews and observation methods for qualitative research, as well as tests to measure the effectiveness of the motion graphic media being developed. At the qualitative stage, this research found the need to develop interactive audio-visual media. This research shows the values ​​of prophetic education and establishes its connection with the pillars of positive politeness. Values ​​are divided based on humanization (amar ma'ruf), liberation (nahi mungkar), and transcendence (tu'minubillah). First, the values ​​of cooperation, generosity, honesty, politeness, and tolerance are included in humanization. Second, the values ​​of education, health, mutual cooperation, and hard work fall into the category of liberation. Third, Istiqomah, the value of worshiping Allah SWT, gratitude, and humility (tawadhu') are grouped under transcendence.